Leadership, Social Cohesion, and Identity in Late Antique Spain and Gaul (500-700) - Ruches, Fernando; Dolores Castro (Ph. D. in history) (Late antique and early medieval Iberia., 2023)
The replacement of the Roman Empire in the West with emerging kingdoms like Visigothic Spain and Merovingian Gaul resulted in new societies, but without major population displacement. Societies changed because identities shifted and new points of cohesion formed under different leaders and leadership structures. This volume examines two kingdoms in the post-Roman west to understand how this process took shape. Though exhibiting striking continuities with the Roman past, Gaul and Spain emerged as distinctive, but not isolated, political entities that forged different strategies and drew upon different resources to strengthen their unity, shape social ties, and consolidate their political status.